Knowledge, Attitude and Doubts of Parents about HEXA Vaccine Newly Introduced in Expanded Program of Immunization in Iraq - Hadeel Fadhil Farhood (Journal of Global Pharma Technology, 2017)
Background a significant number of new effective vaccines against infectious diseases have become available ,some of these vaccines are given in combination as one vaccine , HEXA vaccine is one of these vaccines .the success of vaccination services is dependent not only on vaccines provision but ,also on other factors including parents; knowledge , attitude and also their doubts about the vaccines. Objectives To assess parents' knowledge and attitude about HEXA vaccine newly introduced in expanded program of immunization in Iraq and to identify its parents' doubts .Methods Across sectional interview based study of Iraqi parents in six health sectors in Babylon province -Iraq , during the period of the 1st of March to the 1st of July 2016 ,including (92) parents who had at least one child eligible to be vaccinated with HEXA vaccine (born after 24/11/2015).Parents were interviewed to assess their Knowledge ,Attitude and Doubts about the HEXA vaccine. Results The study found that (38% ) of parents had good Knowledge,(90.2%)had positive attitude, (59.8 %) had doubts about HEXA vaccine.(70.9%) parents had vaccinated their children and they were unsure about the vaccine safety or effectiveness,(29.9 %) parents had delayed their children vaccination ,the main reasons of parents' doubts were Child was ill (44.4%) and(21.8%)don't know enough information about the HEXA vaccine .Conclusions Majority of parents had moderate (fair) knowledge and excellent positive attitude about HEXA vaccine. Most of parents had doubts about HEXA vaccine.Keywords: Knowledge, Attitude, Doubts parents, Expanded program of immunization.